Adjuvant effect of freeze-dried extract of Passiflora edulis (passion fruit) in reducing blood pressure in patients treated with enalapril - Rojas, Juan (2009)
Objectives: To determine the adjunctive antihypertensive effect and safety of passion fruit juice in patients with hypertension treated with enalapril. Design: prospective pilot clinical trial, phase II, randomized, double blind, parallel group, controlled, dose finding and evaluation of the product. Setiing: Instituto de Investigaciones Clínicas, Facultad de Medicina, UNMSM, Dos de Mayo Hospital in Lima, Hospital Belen de Trujillo and Moche and Laredo Health Centers in Trujillo city. Participants: Patients with arterial hypertension. Interventions: Patients were randomly assigned to four groups, each receiving enalapril 10 mg / day; the first group also received placebo and the other, 2, 3 and 4 groups, 500 mg capsules of freeze-dried passion fruit juice / day, respectively. Main outcome measures: Reduction in blood pressure. Results: Groups receiving enalapril and passion fruit had better reduction in blood pressure compared with the group receiving enalapril plus placebo. The group treated with enalapril plus 4 capsules of freezedried passion fruit juice / day had a reduction in systolic blood pressure of 6,73 mmHg and diastolic blood pressure of 5,33 mmHg (p<0,05) compared with the enalapril group more placebo. No adverse effects were observed. Conclusions: P. edulis juice fruit was effective adjuvant to enalapril in reducing blood pressure in patients with stage 1 hypertension, with proved safety